Hubungan Antara Komunikasi Interpersonal Guru Dengan Prestasi Belajar Siswa Kelas Tinggi - Makmur Nurdin; Mujahidah Mujahidah; Andi Tasya Safa Karmila (Jurnal Pendidikan dan Pembelajaran Sekolah Dasar (JPPSD), 2023)
This research is a correlational study which aims to determine the relationship between teacher-student interpersonal communication and student achievement in high grade students. Based on the results of descriptive statistics, it is obtained that the teacher-student interpersonal communication data has an average of 60.15 with a percentage of 64% which is in the medium category and the learning achievement value of high-class students has an average of 85.26 with a percentage of 91% which is included in the very category. good. Based on the results of inferential statistical analysis showed rtabel > at 5% significance level of 0.282 so that rhitung > rtabel (0.315 > 0.282). Thus H_0 is rejected and H_1 is accepted. The conclusion is that there is a significant relationship between students' interpersonal communication and high grade student achievement at SD Inpres 6/75 Manuruge, Tanete Riattang District, Bone Regency.